Pelatihan Penerapan Metode Pengolahan dan Analisis Data Kuantitatif Hasil Penelitian untuk Peningkatan Ketrampilan Penelitian - Hotma Antoni Hutahaean; MM Wahyuni Inderawati; Agustinus Silalahi; Stephen Aprius Sutresno (Jurnal Pengabdian Masyarakat Charitas, 2025)
One of the most important stages in conducting research is processing research data obtained from the data collection process. However, practical understanding regarding the steps for interpreting results and data processing tricks is still limited among general students. To limit this gap, the service team held a workshop related to processing quantitative research data using a statistical application that can be accessed for free via the internet. This activity was successfully implemented and received a positive response from participants. The workshop focuses on providing knowledge and skills related to the use of applications for data processing and interpretation of results using research data that has been used by resource persons in the past. The evaluation results showed that the majority of participants were able to understand the basic concepts of data, data processing and interpretation of results. The workshop shows that the use of examples of actual research data is very effective in bridging theory and practice in conducting research, especially those related to data processing.